The Social Construction of Spinsterhood Among the Pekal Tribe in Napal Putih, North Bengkulu Regency - Safutra, Ferdy; Heriyanti, Lesti; Susiyanto, Susiyanto (Sinthop: Media Kajian Pendidikan, Agama, Sosial dan Budaya, 2025)
This study explores the social construction of spinsterhood among the Pekal Tribe, who predominantly inhabit Napal Putih in North Bengkulu Regency. The research investigates the socio-cultural meanings attached to unmarried women of a certain age and their implications for women's social status and mental well-being in the community. Utilizing a qualitative approach and a case study method, the study involved five Pekalese women—both married and unmarried—as primary informants. Data were collected through interviews and documentation, and validated using source triangulation. The analysis followed the Miles and Huberman framework, involving data reduction, display, and conclusion drawing. The findings reveal that being labeled a spinster is associated with negative connotations in Pekal society, driven by patriarchal culture, limited educational awareness, economic hardship, and strong societal expectations that women marry before the age of 25. These factors collectively shape a perception that unmarried women are socially undesirable. Applying Berger and Luckmann’s Social Construction Theory, the study illustrates how societal norms are formed through externalization, objectification, and internalization, institutionalizing the stigma surrounding spinsterhood. As a result, the concept evolves into a socially constructed label that significantly influences women's opportunities, autonomy, and psychological health within the Pekal community.